Analisis Pelaksanaan Pelelangan Barang Milik Negara di Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) - Anisa; Nuriska; Riska; Farhan, Muhammad Afif; Panaungi, Yasrial Rifqi (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2024)
This study aims to evaluate the effectiveness of the implementation of State Property (BMN) auctions at the State Assets and Auction Service Office (KPKNL) Parepare in increasing state revenues. BMN auctions have an important role in optimizing state assets, either through execution auctions, mandatory non-execution, or voluntary auctions. This study uses a qualitative descriptive method with an interview, observation, and documentation study approach to obtain primary and secondary data. The results of the study indicate that BMN auctions at KPKNL Parepare have made a positive contribution to Non-Tax State Revenue (PNBP), but several obstacles, such as limited budget for socialization, technological infrastructure, and competent human resources, hinder the effectiveness of their implementation. Therefore, this study recommends that the budget for socialization be increased, technological infrastructure be improved, and human resource capacity be strengthened to increase efficiency and transparency in the implementation of BMN auctions.